A two-phase bromination process using tetraalkylammonium hydroxide for the practical synthesis of α-bromolactones from lactones - Yamamoto, Yuki; Tabuchi, Akihiro; Hosono, Kazumi; Ochi, Takanori; Yamazaki, Kento; Kodama, Shintaro; Nomoto, Akihiro; Ogawa, Akiya (Beilstein Journal of Organic Chemistry, 2021)
A simple and efficient method for α-brominating lactones that affords α-bromolactones under mild conditions using tetraalkylammonium hydroxide (R4N+OH−) as a base was developed. Lactones are ring-opened with Br2 and a substoichiometric amount of PBr3, leading to good yields of the corresponding α-bromocarboxylic acids. Subsequent intramolecular cyclization over 1 h using a two-phase system (H2O/CHCl3) containing R4N+OH− afforded α-bromo lactones in good yields. This method can be applied at the 10 mmol scale using simple operations. α-Bromo-δ-valerolactone, which is extremely reactive and difficult to isolate, could be isolated and stored in a freezer for about one week using the developed method. Optimizing the solvent for environmentally friendly large-scale syntheses revealed that methyl ethyl ketone (MEK) was as effective. In addition, in situ-generated α-bromo-δ-valerolactone was directly converted into a sulfur-substituted functional lactone without difficulty by reacting it with a sulfur nucleophile in one pot without isolation. This new bromination system is expected to facilitate the industrial use of α-bromolactones as important intermediates.
Keywords: α-bromolactone; metal-free; one-pot operation; tetraalkylammonium hydroxide; two-phase system